The impact of interferon‐free direct‐acting antivirals on clinical outcome after curative treatment for hepatitis C virus–associated hepatocellular carcinoma: Comparison with interferon‐based therapy. Issue 4 (19th November 2018) - Nagaoki, Yuko; Imamura, Michio; Nishida, Yuno; Daijo, Kana; Teraoka, Yuji; Honda, Fumi; Nakamura, Yuki; Morio, Kei; Fujino, Hatsue; Nakahara, Takashi; Kawaoka, Tomokazu; Tsuge, Masataka; et al.
Abstract: Background and Aim: To examine the effect on recurrence and survival of treatment by interferon (IFN)‐free direct‐acting antivirals (DAA) for patients with hepatitis C virus (HCV)‐associated hepatocellular carcinoma (HCC) who underwent primary curative treatment. Methods: This was a retrospective cohort study of 250 patients with HCV who had received curative treatment for primary HCC. As anti‐HCV treatment after HCC treatment, 38 patients received IFN‐free DAA therapy (DAA patients) and 94 received IFN‐based therapy (IFN patients). The recurrence of HCC and overall survival of the patient groups were compared in a case‐control study. Results: The cumulative HCC recurrence rates at 1, 3, and 5 years were 5%, 39%, and 39% for DAA patients and 0%, 46%, and 62% for IFN patients, respectively ( P = 0.370). Multivariate analysis of the HCC recurrence identified treatment responses (sustained virological response [SVR]: hazard ratio [HR] 2.237; P = 0.003) as an independent predictive factor. The cumulative overall survival rates at 3 and 5 years were 96%, 96% for DAA patients and 93%, 73% for IFN patients, respectively ( P = 0.163). Multivariate analysis identified treatment responses (SVR: HR 8.742; P < 0.001) as independent predictors of overall survival. Propensity score matching analysis showed no significant difference in HCC development rates and overall survival rates in the two groups. Conclusions: We found that SVR obtained after curative treatment for primary HCC suppressed recurrence and improved overall survival. And, IFN‐free DAA therapy after curative treatment for primary HCC could predict improving overall survival and suppressed HCC recurrence.